1997
DOI: 10.1080/00438243.1997.9980364
|View full text |Cite
|
Sign up to set email alerts
|

Prehispanic human ecology of the Río Verde drainage basin, Mexico

Abstract: This article discusses the results of ten years of interdisciplinary archaeological research along the Río Verde drainage basin, Oaxaca, Mexico. In the highland valleys of the upper drainage basin we have documented six periods of significant geomorphic change. The first two were probably the result of climatic change during the mid-Holocene. The four subsequent periods of landscape change are correlated with major shifts in demographics and human land use; we argue that these factors may be causally related. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…There have been paleoenvironmental and geomorphic studies done in the Coixtlahuaca Valley (Rincón Mautner 1999), the Nochixtlán Valley (Mueller et al 2012) and the area surrounding Cerro Jazmín (Kirkby 1972;Pérez Rodríguez et al 2011), and the lower Río Verde Valley (Goman et al 2005;Joyce and Mueller 1997). Joyce and Mueller (1997;Goman et al 2005) conducted a study of geomorphic transformations in the highlands and found chronological correspondence with demographic shifts and changes in land-use practices in the highlands that led to changes in alluvial deposition and river morphology in the lower Río Verde. Researchers identified six episodes of geomorphic transition.…”
Section: Environmental Studiesmentioning
confidence: 98%
“…There have been paleoenvironmental and geomorphic studies done in the Coixtlahuaca Valley (Rincón Mautner 1999), the Nochixtlán Valley (Mueller et al 2012) and the area surrounding Cerro Jazmín (Kirkby 1972;Pérez Rodríguez et al 2011), and the lower Río Verde Valley (Goman et al 2005;Joyce and Mueller 1997). Joyce and Mueller (1997;Goman et al 2005) conducted a study of geomorphic transformations in the highlands and found chronological correspondence with demographic shifts and changes in land-use practices in the highlands that led to changes in alluvial deposition and river morphology in the lower Río Verde. Researchers identified six episodes of geomorphic transition.…”
Section: Environmental Studiesmentioning
confidence: 98%
“…Heine thus aligned himself with the earliest and still most common class of explanations of land degradation, which Blaikie and Brookfield (:28) referred to as PPR (pressure of population on resources) explanations. PPR has been invoked to explain environmental change elsewhere in Mexico, especially in early studies of broad geographical scope (Cook, , ) or based on large sediment sinks (O'Hara, Street, & Burt, ; Joyce & Mueller, ).…”
Section: Cyclical and Irreversible Landscape Changementioning
confidence: 99%
“…Geomorphological research has continued in the lower Río Verde Valley (Joyce and Mueller 1997, Mueller et al, Chapter 3) as well as in the highland valleys of Oaxaca, Nochixtlán, and ejutla, which make up most of the Verde's upper drainage basin (Mueller and Pou 2008;Mueller et al 2012). The research suggests that human land use in the highlands triggered geomorphic changes that may have affected the entire drainage.…”
Section: History Of Archaeological Researchmentioning
confidence: 99%
“…The data indicate that population growth and agricultural expansion in the highlands during the early Formative period accelerated anthropogenic erosion into the drainage basin. Sediment carried down the drainage system to the coast triggered major shifts in the geomorphology of the lower valley, including changes in river morphology and the expansion of the Río Verde's agriculturally productive floodplain (Joyce and Mueller 1997;Mueller et al, Chapter 3). Paleoecological studies by Michelle Goman and colleagues (Goman et al 2005 show that coastal environments were also affected by the increased sediment load carried down from the highlands.…”
Section: History Of Archaeological Researchmentioning
confidence: 99%